Reading the Bible with the Founding Fathers - Dreisbach, Daniel L. 1959- (New York, NY Oxford University Press, 2017)
Dreisbach shows that the Bible was the most frequently referenced book in the political discourse of the American founders. Drawing on some of the most familiar rhetoric of the founding era, 'Reading the Bible with the Founding Fathers' examines the founders' diverse uses of the Bible and how scripture informed their political culture
Includes bibliographical references and index
Previously issued in print: 2017
Zielgruppe - Audience: Specialized
Keywords: Bible and politics -- United States -- History -- 18th century; Founding Fathers of the United States -- Religious life; Bible and politics ; United States ; History ; 18th century; Founding Fathers of the United States ; Religious life; United States ; Politics and government ; 1775-1783; United States -- Politics and government -- 1775-1783